Nutritional, lifestyle, and weight control practices of professional jockeys - Dolan, E.; O'Connor, H.; McGoldrick, A.; O'Loughlin, G.; Lyons, D.; Warrington, G. (Journal of Sports Sciences, 2011)
In this study, we describe diet and lifestyle practices of professional jockeys. Participants completed a 59-item nutrition, lifestyle, and health questionnaire (n = 21) and a 7-day estimated food diary (n = 18). Acute weight loss strategies included the use of saunas (86%), exercising to induce sweating (81%), and restricted energy intake (71%). Of the smokers (38%), 56% used smoking to control weight. Most (86%) jockeys reported attaining a 2-kg weight loss for racing (if required) 24-48 h before or on the designated race-day. Mean daily energy intake (1803 ± 564 kcal) was low and appeared to provide an insufficient availability of energy for sustainment of usual daily and metabolic processes. Carbohydrate intake (3.7 ± 1.3 g · kg-1) was below recommendations for athletes. A substantial proportion of jockeys failed to meet the estimated average requirement and lower threshold intake for a number of micronutrients. Jockeys consumed well below (0-2) the recommended five daily servings of fruit and vegetables set by the World Health Organization. Pressures of the jockey lifestyle and rigid weight limits appear to encourage unhealthy weight management practices in this group and may risk long term-health.